2016
DOI: 10.1177/0266666916638136
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the drivers of mobile learning acceptance among young adults in the World Heritage town of Luang Prabang, Laos

Abstract: This study is motivated by the initiative to implement mobile learning to promote world heritage site awareness among young adults living in the world heritage town of Luang Prabang in the Lao People's Democratic Republic (PDR). Mobile learning is still in its infant stage in Laos. The objective of this study is to investigate the drivers of mobile learning acceptance among young adults in Luang Prabang. Structural equation modeling analysis based on 349 students of higher education indicates that perceived us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
64
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(74 citation statements)
references
References 53 publications
10
64
0
Order By: Relevance
“…Therefore, H1 and H2 were supported. These findings are consistent with the findings of Chung et al (2015) and Poong et al (2017) who found that self efficacy had a significant positive influence on perceived ease of use and perceived usefulness. Further, system quality had a significant effect on perceived ease of use (ß = 0.269 p = 0.000) and perceived usefulness (ß = 0.285 p = 0.000) of mobile learning, meaning when the information provided and the efficiency of the m-Learning system is high, it will enhance the students" feeling that m-Learning system is useful for their learning and that it is easy to use.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Therefore, H1 and H2 were supported. These findings are consistent with the findings of Chung et al (2015) and Poong et al (2017) who found that self efficacy had a significant positive influence on perceived ease of use and perceived usefulness. Further, system quality had a significant effect on perceived ease of use (ß = 0.269 p = 0.000) and perceived usefulness (ß = 0.285 p = 0.000) of mobile learning, meaning when the information provided and the efficiency of the m-Learning system is high, it will enhance the students" feeling that m-Learning system is useful for their learning and that it is easy to use.…”
Section: Discussionsupporting
confidence: 92%
“…According to the study on college students" acceptance of mobile learning conducted by Chung, Chen & Kuo (2015), it was found that self-efficacy had a significant influence on perceived ease of use and perceived usefulness. Poong, Yamaguchi & Takada (2017) in their study on drivers of mobile learning acceptance among young adults in Laos also found that self-efficacy had a significant influence on perceived ease of use and perceived usefulness. Based on that, mobile self-efficacy in this research study is hypothesized to have a direct impact on the perceived usefulness and the ease of use.…”
Section: Mobile Self-efficacymentioning
confidence: 91%
“…This coincides with the findings by Baptista and Oliveira (2015) , Savita Panwar (2017) , and Sivathanu (2018) , who found that HM has a significant impact on the intention to use m-banking, mobile shopping app, and digital payment systems, and reinforces the claim of authors such as Alalwan et al. (2016) , Morosan and DeFranco (2016) , Poong et al. (2016) and Venkatesh et al.…”
Section: Discussionsupporting
confidence: 90%
“…The present research also confirmed that the perception of using mcommerce as an entertaining and fun experience has a direct and positive impact on the intention to use the m-commerce by low-income Ecuadorian consumers. This coincides with the findings by Baptista and Oliveira (2015), Savita Panwar (2017), and Sivathanu (2018), who found that HM has a significant impact on the intention to use m-banking, mobile shopping app, and digital payment systems, and reinforces the claim of authors such as Alalwan et al (2016), Morosan and DeFranco (2016), Poong et al (2016) and Venkatesh et al (2012) that hedonic benefits are essential drivers of intention to use or adopt information technologies.…”
Section: Pe Sisupporting
confidence: 89%
See 1 more Smart Citation